THE REALIZATION OF GRAMMATICAL COHESION DEVICES IN EFL STUDENTS’ ARGUMENTATIVE ESSAYS - Rudiana Rudiana (JALL (Journal of Applied Linguistics and Literacy), 2021)
This study analyzed EFL students’ argumentative essays concerning cohesive devices based on Halliday and Hasan (1976) in the certain part called grammatical cohesion devices. Thus, the study focuses on analyzing the four main categories of them. Those are (1) reference, (2) substitution, (3) ellipsis, and (4) conjunction. Moreover, this study was aimed at figuring out the realization of grammatical cohesion devices which was centred on determining the type of those devices, the predominant devices realized, and the extent to which the use of those devices helps the texts achieve their cohesion. Moreover, this study employed a descriptive qualitative method. Furthermore, the analysis revealed three main points. Firstly, there were grammatical cohesion devices realized on the EFL students’ argumentative essays such as reference, ellipsis, and conjunction. Secondly, the predominant devices were personal reference and additive conjunction. Finally, the use of grammatical cohesion devices could effectively enhance the quality of students’ writing; it could create the relation and connectedness between one element and another in the text as well. In brief, this study presented deep comprehension about grammatical cohesion devices which covered reference, substitution, ellipsis, and conjunction. Therefore, the use of those could completely improve the quality of writing especially an argumentative essay.  Keywords: grammatical cohesion devices, EFL students’ argumentative essay